Enriching the evidence base of co-creation research in public health with methodological principles of critical realism - Katrina Messiha; Teatske M Altenburg; Margrit Schreier; Giuliana R Longworth; Nicole Thomas; Sebastien Chastin; Mai JM Chinapaw (Taylor & Francis Group, 2024)
With the popularity of co-creation research in public health and other fields, there is a need to strengthen its evidence-base by developing a framework based on meta-theoretical principles. The lack of applying meta-theoretical principles in co-creation research impedes the theory- and evidence building. Critical realism seems a promising candidate for providing meta-theoretical principles to enrich the evidence base of co-creation research in public health. To this purpose we searched for relevant papers on critical realism methodological principles, clarified and subsequently applied such principles to a co-creation public health case study. We provide explanatory steps to apply five principles; 1) focusing on understanding an event, like childhood overweight, 2) exploring the broader structure and context surrounding the event, 3) constructing hypotheses about the underlying mechanism(s) of an event, 4) empirical testing to corroborate those hypotheses, and 5) using multiple methods and triangulation. Further, this study shows that critical realism can enrich co-creation research in public health by iteratively building theory and evidence following the five proposed principles.